Angklung as an Instrument of Paradiplomacy: A Case Study on the Sister Province Relations of West Java-Sichuan and West Java-Chungcheongnam-do - Athallah, Muhammad Raja; Sari, Deasy Silvya (Universitas Muhammadiyah Yogyakarta, 2025)
West Java’s rich cultural heritage presents immense potential for the province’s advancement. The active paradiplomacy that West Java fosters with various international provinces significantly amplifies the potential utilization of its cultural assets. West Java stands out as one of Indonesia’s provinces with high and effective paradiplomacy activities. In conjunction with West Java’s ongoing paradiplomatic processes, the angklung emerges as an instrument embodying the value of unity and harmony. Sichuan and Chungcheongnam-do served as key respondents for observing the implementation of the angklung as an instrument in West Java’s paradiplomacy. The strong relationship between West Java and its two sister provinces has led to the renewal of the Memorandum of Understanding and the effective continuation of collaborative programs within their active cooperation periods. The utilization of the angklung, originating from West Java, offers insights into how soft power operates within the paradiplomacy. The direct link between paradiplomacy and soft power made this research particularly compelling. Drawing from the participant observation method conducted by the researchers as part of West Java’s efforts, this study focuses on the correlation between the angklung and the values championed in West Java’s paradiplomacy with its two sister province partners.